Transforming Arabic Writing Skills through Qur’anic Expression Pattern-Based Insha’ Materials: A Developmental Study - Qintan Emilia Sholihah; Umar Faruq; Ahmad Taufiq (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
The scarcity of specialized textbooks in Arabic writing instruction often leads to creative stagnation and a heavy reliance on passive translation methods at the secondary school level. This study aims to develop and evaluate the effectiveness of composition instructional materials adapted from Dr. Nasaruddin Idris Jauhar’s methodology of Qur’anic expression patterns to enhance students’ writing proficiency. Employing a Research and Development (R&D) approach with the ADDIE model, the study involved 70 eleventh-grade students at SMA Al-Ishlah Ngasem Kediri. Expert validation results categorized the product as “Very Feasible” with a mean score of 83.84%. Inferential analysis using an independent samples t-test demonstrated a significant improvement in writing skills; the experimental group achieved a post-test mean of 86.76, substantially outperforming the control group’s mean of 80.00 (p < 0.001). In conclusion, utilizing authentic Qur’anic expression patterns as a cognitive framework is effective in transforming writing abilities from mere word reproduction to creative text production. This research offers a theoretical contribution to reconstructing core content based on authoritative text authenticity and a practical contribution by providing an innovative module to overcome Arabic literacy barriers in schools.